Artista/Câmara de maravilhas - Brengel, Ana Maria Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present dissertation has two different purposes: to register the artist’s production – including sculptures, objects, installations, paintings, performances, artistic experiences – and to present a theoretical text. For both cases, the research focuses on the exhibition space and how art works are exhibited, comparing the present spaces for exhibition and the Cabinets of Curiosities – private collections presented to a selected public, mostly during the 17th and 18th centuries, which can be regarded as the predecessors of modern museums

Esta dissertação tem dois resultados distintos: minha produção artística, envolvendo esculturas, objetos, instalações, pinturas, performances, vivência artística e um texto teórico. Em ambos os casos, o assunto da pesquisa é sobre o espaço de exposição e o modo como as obras de arte são exibidas, comparando os locais expositivos atuais e suas especificidades aos chamados Gabinetes de Curiosidades – coleções privadas exibidas a um público seleto, sobretudo entre os séculos XVII e XVIII, que podem ser considerados precursores dos museus modernos
Keywords: Arte; Performance (Arte); Pintura; Museologia; Performance art